(untitled) (Economic studies journal, 2025)
This study aims to explore the role of digital transformation in enhancing financial control systems at the Libyan Audit Bureau, particularly in light of the challenges faced by traditional systems, such as audit delays, weak infrastructure, and a lack of digital competencies، The study focused on four dimensions of digital transformation: human resources, computer systems and software, networks and databases, and cybersecurity, assessing their individual and collective impact on improving financial oversight in terms of accuracy, efficiency, effectiveness, and transparency. A questionnaire was distributed to a sample of Audit Bureau employees, and data were analyzed using statistical tools such as mean, standard deviation, and regression analysis، The results revealed a statistically significant positive relationship between digital transformation and the development of financial control systems, with the model explaining 58% of the variance، All four digital dimensions were found to positively influence financial oversight performance to varying degrees. The researcher recommended the need to promote digital transformation with new technologies because of their role in improving financial control and facilitating audit processes, to ensure improved audit quality and greater transparency in public financial management.